Olfaction in chemotherapy for head and neck malignancies. Issue 1 (February 2016) - Haxel, Boris R.; Berg, Stephanie; Boessert, Patrick; Mann, Wolf J.; Fruth, Kai
Abstract: Objective: Systemic chemotherapy for different malignancies occurs alongside various side effects, including reduced sensory function. To date, little is known about the effect of chemotherapeutic agents on olfaction. The aim of this study was to provide new data about changes in sense of smell during chemotherapy among patients with advanced squamous cell carcinomas of the head and neck region. Methods: In a prospective, controlled cohort study of patients undergoing up to three courses of chemotherapy (cis- or carboplatin, 5-fluorouracil and docetaxel), olfaction was evaluated prior to and directly following completing a cycle, as well as 3 weeks later with the beginning of the next cycle. For evaluation of sense of smell, the established Sniffin' Sticks test with a determination of threshold, discrimination and identification (TDI) was used. Thirty-three patients (44–85 years old, 25 men and 8 women) were included in the study. Most malignancies were located in the oropharynx. Results: Among the 28 patients who scored normosmic or hyposmic at the beginning of the study, the mean decrease in TDI-score was 0.72 points (24.0–23.2) in the first cycle, 2.1 points (24.5–22.4) in the second cycle and 0.77 points (24.2–23.4) in the third cycle. The decrease during the second cycle was significant. Age (>55 years) had a significant (negative) influence in the first and the second cycles. Smoking only showed a tendency to decreased TDI-scores in chemotherapy. In-between consecutive cycles an increase in TDI-score was obvious (+1.0 points after the first and +1.5 points after the second cycle). Conclusion: Chemotherapy with cisplatin, 5-fluorouracil and docetaxel significantly affected sense of smell to a small extent. This effect was more pronounced in elderly patients and smokers. This fact must be taken into account as a possible additional negative effect in usually prevailing malnutrition in these patients. Furthermore, no cumulative effect of the administered therapeutic agents on olfaction could be proven during this study and recovery occurred within a 3-week period.